2015
DOI: 10.1007/s10439-015-1418-0
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Hydroxyapatite Content Affects the Cell Differentiation on Porous Chitosan/Hydroxyapatite Scaffolds

Abstract: Highly porous chitosan/hydroxyapatite composite structures with different weight ratios (100/0; 90/10; 80/20; 70/30; 60/40; 50/50; 40/60) have been prepared by precipitation method and freeze-gelation technique using calcite, urea phosphate and chitosan as starting materials. The composition of prepared composite scaffolds was characterized by X-ray diffraction analysis and Fourier transformed infrared spectroscopy, while morphology of scaffolds was imaged by scanning electron microscopy. Mercury intrusion por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
(32 reference statements)
0
16
0
8
Order By: Relevance
“…3a, b). The mean size of HA-0.5, HA-1, and HA-2 scaffolds was >100 μm, which was within the recommended pore size range for bone regeneration [Rogina et al, 2016]. The addition of HA induced a concentration-dependent increase in the compressive modulus of the scaffolds (Fig.…”
Section: Characterization Of Scaffolds With Different Ha Contentsmentioning
confidence: 99%
“…3a, b). The mean size of HA-0.5, HA-1, and HA-2 scaffolds was >100 μm, which was within the recommended pore size range for bone regeneration [Rogina et al, 2016]. The addition of HA induced a concentration-dependent increase in the compressive modulus of the scaffolds (Fig.…”
Section: Characterization Of Scaffolds With Different Ha Contentsmentioning
confidence: 99%
“…Our previous studies [18,19] have indicated highly porous chitosan-based scaffolds with 30% weight ratio of in situ formed hydroxyapatite as a suitable environment for differentiation of MC3T3-E1 preosteoblasts during 14 days of culture. In situ synthesis has provided good dispersion of formed HA particles and formation of nonstoichiometric more bioresorbable hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…As análises de FTIR foram realizadas com o objetivo de identificar os grupos funcionais específicos tanto para os extratos secos de própolis verde e vermelha como para as amostras (HA-ETOH80, HA-GP20, HA-GP8, HA-RP20 e HA-RP8). Para os extratos secos de própolis verde e vermelha, os espectros de FTIR foram obtidos com objetivo principal de identificar grupos funcionais característicos de fenólicos e flavonoides totais, principais responsáveis pela atividade antimicrobiana destes extratos, uma vez que a composição da própolis é bastante complexa e variável, apresentando mais de 300 substâncias (SFORCIN, 2016 adsorvido da atmosfera durante o processo de síntese, uma vez que o procedimento é realizado em sistema aberto (GUERRA-LOPEZ et al, 2015;HE;DONG;DENG, 2016;JAFARI et al, 2016;ROGINA et al, 2016;SINGH, 2016;ZHANG et al, 2016). A Tabela 8 mostra os sinais obtidos para cada banda de absorção para a amostra HA-ETOH80 e suas respectivas atribuições.…”
Section: Caracterização Dos Materiaisunclassified
“…Nos espectros obtidos para as amostras HA-GP 20 e HA-GP8 ( Guerra-Lopez et al (2015); Rogina et al (2016); Srilakshmi, Saraf (2016); Zhang et al (2016) Fonte: Própria autoria.…”
Section: Caracterização Dos Materiaisunclassified